2018
DOI: 10.3390/nu10060773
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Multispecies Probiotic Supplementation on the Lipopolysaccharide (LPS) Level and Cardiometabolic Profile in Obese Postmenopausal Women: A 12-Week Randomized Clinical Trial

Abstract: During the postmenopausal period, the risk of cardiovascular diseases is increased in many obese women and is associated with a worse cardiometabolic profile and a sub-chronic low-grade systemic inflammation caused by a gut barrier permeability dysfunction. Here, we tested whether administration of two different dosages of the multispecies probiotic Ecologic® Barrier influenced the cardiometabolic biochemical parameters and lipopolysaccharide levels, the latter used as a marker of increased gut permeability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(187 citation statements)
references
References 47 publications
5
172
1
9
Order By: Relevance
“…The supplementation of Ecologic ® Barrier (2.5 × 10 9 or 1 × 10 10 CFU/day) for 12 weeks improved the TG and LDL-C content and other metabolic and cardiovascular disease parameters in obese postmenopausal women [39].…”
Section: Other Subjectsmentioning
confidence: 95%
See 2 more Smart Citations
“…The supplementation of Ecologic ® Barrier (2.5 × 10 9 or 1 × 10 10 CFU/day) for 12 weeks improved the TG and LDL-C content and other metabolic and cardiovascular disease parameters in obese postmenopausal women [39].…”
Section: Other Subjectsmentioning
confidence: 95%
“…Based on the randomized, placebo-controlled, double-blind studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] reviewed in the present article, the hypocholesterolemic effect of the probiotics was not significantly influenced by the diet. Studies reported based on the intervention of single-strain probiotic (E. faecium M-74 along with selenium [27]; Saccharomyces cerevisiae var.…”
Section: Opinion On the Hypocholesterolemic Effect Of Reviewed Probiomentioning
confidence: 99%
See 1 more Smart Citation
“…Cani et al [170] in an animal model study noted that in response to an HFD, the plasma LPS level increased. The higher LPS concentration is associated with the development of obesity and insulin resistance [171]. On the other hand, an increased LPS level and obesity have been observed in mice fed a control diet after LPS infusion.…”
Section: Metabolic Endotoxemiamentioning
confidence: 99%
“…In the study by Hertzler and Clancy the concomitant use for one day of L. lactis, Lactobacillus plantarum, Streptococcus cremoris, Lactobacillus casei, Streptococcus diacetylactis, Saccharomyces florentinus and Lactococcus cremoris improved the tolerance and digestibility of lactose in people with impaired lactose digestion [10]. Probiotic have shown beneficial properties in obese patients [17]. Obese postmenopausal women supplementing a probiotic preparation for 12 weeks had improved parameters, such as waist circumference, body fat mass, amount of subcutaneous fat, as well as the lipid profile and carbohydrate metabolism [17].…”
Section: Introductionmentioning
confidence: 99%